Let’s get functional: drug sensitivity profiling to enable precision sarcoma medicine - Ball, Claudia R.; Fröhling, Stefan (Cell stem cell, 2024)
Drug sensitivity profiling in patient-derived tumor models offers new hope for improving outcomes in cancers lacking effective therapies. Al Shihabi et al.1 demonstrate that short-term cultures from bone and soft tissue sarcomas enable clinically meaningful screening of multiple drugs and combinations, marking a significant advance in personalized care for these high-risk diseases.